Multicompartmental, multilayered probucol microcapsules for diabetes mellitus: Formulation characterization and effects on production of insulin and inflammation in a pancreatic ß-cell line - Mooranian, A.; Negrulj, R.; Arfuso, Frank; Al-Salami, H. (2015)
CONTEXT: We have shown that the primary bile acid, cholic acid (CA), has anti-diabetic effects in vivo. Probucol (PB) is a lipophilic drug with potential applications in type 2 diabetes (T2D). OBJECTIVE: This study aimed to encapsulate CA with PB and examine the formulation and surface characteristics of the microcapsules. We also tested the microcapsules' biological effects on pancreatic ß-cells. METHODS: Using the polymer, sodium alginate (SA), two formulations were prepared: PB-SA (control), and PB-CA-SA (test). Complete characterizations of the morphology, shape, size, chemical, thermal, and rheological properties, swelling and mechanical strength, cross-sectional imaging (Micro CT), stability, Zeta-potential, drug contents, and PB release profile were carried out, at different temperature and pH values. The microcapsules were applied to a NIT-1 cell culture and the supernatant was analyzed for insulin and TNF-a concentrations. RESULTS: CA incorporation optimized the PB microcapsules, which exhibited pseudoplastic-thixotropic rheological characteristics. The size of the microcapsules remained similar after CA addition, and the microcapsules showed even drug distribution and no chemical alterations of the excipients. Micro-CT imaging, differential scanning calorimetry, Fourier transform infrared spectroscopy, scanning electron microscopy, and energy-dispersive X-ray spectroscopy showed consistent microcapsules with uniform shape and morphology. PB-CA-SA microcapsules enhanced NIT-1 cell viability under hyperglycemic states and resulted in improved insulin release as well as reduced cytokine production at the physiological glucose levels. CONCLUSIONS: The addition of the primary bile acid, CA, improved the physical properties of the microcapsules and enhanced their pharmacological activity in vitro, suggesting potential applications in diabetes treatment.